PERAN BAITUL MAL DALAM PENGUMPULAN DAN PENDISTRIBUSIAN ZAKAT PADA PNS KABUPATEN PIDIE: Studi Kasus di Baitul Mal Kab Pidie - Amri Amri (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
This scientific paper discusses "The Role of the Baitul Mal in Collecting and Distributing Zakat (Case Study in the Baitul Mal of Pidie District)." In order to examine the three fundamental problems of the collection and distribution of zakat at the Baitul Mal Pidie District, the role of the Baitul Mal is in the collection and distribution zakat and the problems faced by baitul mal officers in collecting and distributing zakat. The research aims to obtain an overview as mentioned above. Research data obtained in the field, researchers used several ways, namely field research (Field Research), using observation techniques, questionnaires, interviews, and documentation, as well as Research Library (Library Research). The results showed that the mechanism for collecting and distributing zakat, in which the treasurers of each government agency in Pidie Regency deposited directly to the regional treasury according to established provisions, while the distribution of zakat was channeled: to the destitute, poor, gharim, converts, ibnu sabil and other mustahiq in need. Whereas the implementation and role of the Baitul Mal in collecting and distributing zakat was carried out by the Baitul Mal Pidie Regency by disseminating information to the community and inviting all relevant agencies in the local government to make various breakthroughs to make people aware of their obligations as zakat, while no problems were found , because the collection of zakat is carried out only on civil servants, and also in the process of distributing zakat there are already established technical instructions.